2021
DOI: 10.1111/jan.14872
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and self‐regulation failure: A diary study of self‐undermining and job crafting among nurses

Abstract: Aim The objective was to test how nurse burnout impairs day‐to‐day adaptive self‐regulation strategies that link levels of regulatory resources with employee job performance. Background Regulatory resources help employees manage their thoughts, feelings, and behaviours on a daily basis. On days when these resources are low, employees may engage in maladaptive self‐regulation: more self‐undermining (i.e. creating additional obstacles) and less job crafting (i.e. optimizing job demands and resources), which debi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 92 publications
0
39
0
Order By: Relevance
“…Burnout may not be related to work‐life balance significantly, but it affects the whole life of the employees by triggering negative emotions (Roth et al, 2021). The study of Roczniewska and Bakker (2021) showed that burnout affects the day‐to‐day behaviour regulation of nurses negatively. Consequently, the employees experiencing burnout try to avoid it due to their protective instincts, and they will tend to quit.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout may not be related to work‐life balance significantly, but it affects the whole life of the employees by triggering negative emotions (Roth et al, 2021). The study of Roczniewska and Bakker (2021) showed that burnout affects the day‐to‐day behaviour regulation of nurses negatively. Consequently, the employees experiencing burnout try to avoid it due to their protective instincts, and they will tend to quit.…”
Section: Introductionmentioning
confidence: 99%
“…Somethings matter to the individual that cares, and this involvement is a compass for being in the world but also put people at risk and make them vulnerable. It is known that not being able to bestow care in line with internal and external expectations put nurses at risk of developing moral stress and troubled conscience (Ericson‐Lidman et al, 2013 ; Glasberg et al, 2007 ; Juthberg Eriksson et al, 2010 ; Lidman & Strandberg, 2020 ; Mazaheri Ericson‐Lidman et al, 2018 ; Roczniewska & Bakker, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…(SWJS) as well as moderate dispositional optimism including 34.93% nurses with pessimistic, 37.41 with neutral and 27.66 with optimistic life orientation (LOT-R). A study by Roczniewska and Bakker 33 has shown that chronic burnout among nurses disrupts daily behavioral regulation. Individuals with elevated burnout symptoms have difficulty translating transient increases in regulatory resources into adaptive strategies associated with higher performance.…”
Section: Discussionmentioning
confidence: 99%